Pengaruh Suhu dan Lama Penyimpanan Terhadap Karakteristik Fisikokimia, Organoleptik dan Mikrobiologis Jruek Drien (Durian Fermentasi Khas Aceh) - Eva Murlida; Cut Wirna Wilfida; Asmawati Asmawati (Agricultural Faculty, 2022)
Durian is a horticultural product that is easily damaged so it needs to be processed into other products. One of them can be processed into jruek drien. Jruek drien is one of the efforts made to extend the shelf life by means of fermentation. The purpose of this study was to determine the effect of temperature and duration of storage time on the physicochemical, microbiological and organoleptic on jruek drien characteristic. This study used a factorial randomized block design with two factors, namely the storage temperature with two level (room temperature and refrigerator temperature) and storage time with three levels (3, 6, 9 days) with 3 replicatons. The average value of each parameter is pH 4,1, total acid 1,26%, total lactic acid bacteria 7,14 log CFU/g and organoleptic values of color, aroma, taste and texture are 3.24 (neutral), 2.71 (neutral), 2.63 (neutral), 3.08 (neutral) respectively. Temperature and storage time and their interaction greatly affect the pH and total acid in the juicer. Temperature significantly affected the total lactic acid bacteria and organolepti test of color and aroma. The best result in making jruek drien is refrigerator temperature storage with six days of storage.